The Risk of Major Adverse Cardiovascular Events in Ankylosing Spondylitis Patients With a History of Acute Anterior Uveitis: A Nationwide, Population Based Cohort Study - Bai, Yi-Chiao; Liu, Chin-Hsiu; Leong, Pui-Ying; Lai, Kuo-Lung; Chen, Hsin-Hua; Wei, James Cheng-Chung (Frontiers in Medicine, 2022)
Background To investigate the association between a history of acute anterior uveitis (AAU) and the risk of major adverse cardiovascular events (MACE) among patients with ankylosing spondylitis (AS). Methods We identified 38,691 newly diagnosed AS patients between 2003 and 2013 from the Taiwan National Health Insurance Research Database. The exposure group was defined as people with uveitis diagnosis by ophthalmologist before AS diagnosis date. The incidence of MACE in patients with AS according to the International Classification of Diseases, Ninth Revision. We randomly selected a comparison group without a history of AAU at a 1:4 ratio matched by age, sex, and index year in relation to the risk of developing MACE. We used cox proportional hazard regression model to compare the risk of MACE between groups, shown as adjusted hazard ratios (aHRs) with 95% confidence intervals (CI). Further subgroup analysis and sensitivity tests were also performed. Results There were 3,544 patients in the AAU group and 14,176 patients in the non-AAU group. The aHR of MACE for the AAU group was 0.79 (95% CI = 0.57–1.10) at a 1:4 ratio for age, sex and index year. Sensitivity analyses using various adjustment variables showed consistent results. Cox proportional hazard regression model demonstrated that use of non-steroidal anti-inflammatory drugs (NSAIDs) was associated with an increased risk of MACE in this cohort (HR = 3.44; 95% CI = 2.25–5.25). Conclusion This cohort study showed that subjects with AAU was not associated with the risk of MACE among AS patients, compared to non-AAU controls.